« Tout a un maître » : possession individuelle, usage communautaire de la nature et gestion environnementale participative dans la réserve extractiviste ‘Quilombo do Frechal’ (Brésil) - Manuela Tassan (Amnis)
Through the use of an anthropological perspective, this article intends to show how certain forms of individual appropriation and communitarian use of nature may not only coexist, but also represent a strong element of social identification within a so-called « traditional community » in the Brazilian Amazonia. Moreover, this text also highlights the consequences of an approach adopted by the local government that does not consider or misunderstands the role of the individual possession of nature. The article suggests, that a stereotyped or ideological approach that leads towards the concept of « commons use » may have unexpected and problematic repercussions upon its implementations process, particularly within protected areas such as extractive reserves that were initially established for social and environmental purposes. Since, these types of Brazilian reserves were built to protect and valorize ordinary human relations with the territory through the promotion of a shared management between government and the local communities. Finally, these questions will be addressed through an analysis of a case in the Reserva Extrativista Quilombo do Frechal (Maranhão, Brazil), currently inhabited by a community of African slaves descendants (quilombo), they are essentially devoted to a slash and burn subsistence agriculture.